Kritikon Litterarum : Internationale Rezensionszeitschrift für Romanistik, Slavistik, Anglistik und Amerikanistik (De Gruyter, 2007)
The journal provides reviews of new publications in the fields of Romance, Slavonic, English, and American literary and cultural studies. It focuses in particular on transdisciplinary topics, aids orientation within the particular subject areas and across the disciplines, and provides an ideal complement to the specialist journals for the subject areas mentioned.